2012
DOI: 10.1002/bab.1054
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of silver nanoparticles using actinobacterium Streptomyces albogriseolus and its antibacterial activity

Abstract: An eco-friendly approach to the synthesis of silver nanoparticles (AgNPs) by extracellular components of Streptomyces albogriseolus has been reported. The isolated actinobacteria were genotypically identified by 16S rRNA sequencing analysis, and the morphology was observed by high-resolution scanning electron microscopy. The preliminary characterization of synthesized nanoparticles was carried out using ultraviolet-visible spectrophotometer. The maximum absorption spectra were found to be 409 nm at the 48th ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Indeed, Candida albicans produced AgCl nanoparticles as shown by XRD pattern, together with Ag o nanoparticles, and the authors unfortunately did not discuss this pattern (Saminathan 2015). Kumar et al (2007) reported the synthesis of Ag°nanoparti-cles from lysozyme, although the XRD analysis confirmed the formation of the Ag°nanoparticles, the authors ignored the presence of AgCl nanoparticles, as revealed by XRD.…”
Section: Yeastsmentioning
confidence: 99%
“…Indeed, Candida albicans produced AgCl nanoparticles as shown by XRD pattern, together with Ag o nanoparticles, and the authors unfortunately did not discuss this pattern (Saminathan 2015). Kumar et al (2007) reported the synthesis of Ag°nanoparti-cles from lysozyme, although the XRD analysis confirmed the formation of the Ag°nanoparticles, the authors ignored the presence of AgCl nanoparticles, as revealed by XRD.…”
Section: Yeastsmentioning
confidence: 99%
“…Biosynthesis of silver nanoparticles (AgNPs) is an eco‐friendly approach by using different biological sources; for example, plants and microorganisms such as bacteria, fungi, and actinobacteria . There are previous reports on Streptomyces sp.—mediated synthesis of silver nanoparticles . Similarly, Narasimha et al successfully synthesized biological AgNPs and confirmed by observing the UV‐vis spectrum of treated cell filtrate of actinobacteria with silver nitrate at about 420 nm.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable number of silver nanoparticles using Streptomyces sp. were reported to show antibacterial activity against varied human pathogens through extracellular mode [14,22,24,29,51,[53][54][55][56][57]. Unnamed actinomycetes mediated silver nanoparticles were also reported to produce antibacterial activity [13,18,44].…”
Section: A Antibacterial Activitymentioning
confidence: 99%